2022
DOI: 10.1021/acs.langmuir.2c00909
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fabrication of Robust and Multifunctional Super Nonwetting Surfaces by Diverse Modifications of Zirconia–Ceria Nanocomposites

Abstract: The creation of surfaces with various super nonwetting properties is an ongoing challenge. We report diverse modifications of novel synthesized zirconia–ceria nanocomposites by different low surface energy agents to fabricate nanofluids capable of regulating surface wettability of mineral substrates to achieve selective superhydrophobic, superoleophobic–superhydrophilic, and superamphiphobic conditions. Surfaces treated with these nanofluids offer self-cleaning properties and effortless rolling-off behavior wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Other studies also reported that hydrophobic surfaces have lower nucleation and growth rates than hydrophilic surfaces. Therefore, designing a multifunctional protective coating allowing simultaneous inhibition of hydrate nucleation and adhesion would be a simple but promising solution for anti-hydrate on a specific substrate surface. It is worth noting that most coatings suffer from low durability under harsh conditions, such as environments with oil pollution or salt corrosion, which results in a significant change in their surface chemistry and a great deterioration in their anti-hydrate performance . Considering the intense repellency to a variety of liquids into consideration, the amphiphobic coating, which is defined as superhydrophobicity and oleophobicity with super anti-wetting properties, would be a potential candidate for durable anti-hydrate in a variety of environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also reported that hydrophobic surfaces have lower nucleation and growth rates than hydrophilic surfaces. Therefore, designing a multifunctional protective coating allowing simultaneous inhibition of hydrate nucleation and adhesion would be a simple but promising solution for anti-hydrate on a specific substrate surface. It is worth noting that most coatings suffer from low durability under harsh conditions, such as environments with oil pollution or salt corrosion, which results in a significant change in their surface chemistry and a great deterioration in their anti-hydrate performance . Considering the intense repellency to a variety of liquids into consideration, the amphiphobic coating, which is defined as superhydrophobicity and oleophobicity with super anti-wetting properties, would be a potential candidate for durable anti-hydrate in a variety of environments.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that most coatings suffer from low durability under harsh conditions, such as environments with oil pollution or salt corrosion, which results in a significant change in their surface chemistry and a great deterioration in their anti-hydrate performance. 17 Considering the intense repellency to a variety of liquids into consideration, the amphiphobic coating, which is defined as superhydrophobicity and oleophobicity with super anti-wetting properties, 18 would be a potential candidate for durable anti-hydrate in a variety of environments. However, to the best of our knowledge, relevant studies regarding anti-hydrates using an amphiphobic coating…”
Section: Introductionmentioning
confidence: 99%